Simultaneous pancreas and kidney transplant: report of the first case performed in Peru - De Vinatea, José (2010)
Simultaneous pancreas and kidney transplantation is the ideal treatment option for patients with type 1 diabetes mellitus with chronic renal failure. Restoring insulin independence and avoiding the need for dialysis dramatically improves the quality of life. Also, the return of euglycemia accomplishes progression and even regression of late diabetes complications, extending overall survival in these patients. These benefits outweigh surgery and immune suppression risks inherent to transplantation. Globally, since 1966 when the first pancreas transplant in Minnesota (United States) was conducted there have been more than 20 000 pancreas transplants with increasing success thanks to the refinement in surgical techniques and new immune suppression schemes. In the present clinical case we report and describe the completion of the first simultaneous pancreas and kidney transplant in Peru.